Penurunan Persentase Kemiskinan Sebagai Dampak Kinerja Keuangan Organisasi Pengelola Zakat di Indonesia - Ezza Aviyani Iman; Dihapri Herli Setyowati; Setiawan Setiawan (Prosiding Industrial Research Workshop and National Seminar, 2018)
The purpose of this research is to analyze knowing the direct and indirect impact among financial performance of zakat management organization to poverty rate in Indonesia with zakat distribution as intervening variable. Financial performance of zakat management organization (OPZ) is proxied by Ritchie and Kolodinsky ratio (2003). They are Fiscal Performance, Public Support and Fundraising Efficiency. The object of this research is central level of Badan Amil Zakat Nasional (BAZNAS) in Jl. Kebon Sirih Raya No. 57. Jakarta Pusat 10340. The constitution of UU No.23 year 2011 is BAZNAS became the coordinator of the implementation of zakat in Indonesia. According to Perpres No.8 year 2001, the report of zakat management by BAZNAS is submitted directly to the president. This research shows the financial performance of BAZNAS has not significantly reduced poverty rate in Indonesia. The advantage of this research for giving the other poverty solution with financial performance of OPZ.